IMPROVING VOCABULARY MASTERY THROUGH SAY STRUCTURE CONTEXT DICTIONARY TECHNIQUE (SSCD) - Dini Sabila Anjanila; Nadrun Nadrun; Mashuri Mashuri (Tadulako University, 2022)
The objective of this research is to investigate the effectiveness of Say Structure Context Dictionary in learning vocabulary at the grade seventh students of SMP Negeri Model Terpadu Madani Palu. This research used pre-experimental research design. The sample of this research was the grade seventh Lamalonda with 21 students that selected by using purposive sampling. The data was collected by administering a vocabulary test conducted before and after the treatment. The result of pre-test and post-test showed that the mean score of pre-test was 32.70 and the mean score of post-test was 76.19. The result of data analysis showed that the t-counted value (4.30) was higher than t-table value (1.725) by applying 0.05 level of significance and 20 degree of freedom (df). In conclusion, the application of Say Structure Context Dictionary in teaching vocabulary is effective improving vocabulary mastery at the grade seventh students’ of SMP Negeri Model Terpadu Madani.